Predictors of Occurrence and 30-Day Mortality for Co-Infection of Carbapenem-Resistant Klebsiella pneumoniae and Carbapenem-Resistant Acinetobacter baumannii - Lv, Dongmei; Zuo, Yan; Wang, Yuerong; Wang, Zhongxin; Xu, Yuanhong (Frontiers in Cellular and Infection Microbiology, 2022)
Abstract Background: The phenomenon of co-infection with multiple carbapenem-resistant bacteria is growing, which pose a great challenge for infection control and treatment. This study aimed to analyze predictors of occurrence and 30-day mortality for carbapenem-resistant Klebsiella pneumoniae and carbapenem-resistant Acinetobacter baumannii co-infection. Methods: From June 2018 to June 2021, clinical data of 103 patients co-infected with carbapenem-resistant Acinetobacter baumannii (CRAB) and carbapenem-resistant Klebsiella pneumoniae (CRKP) were collected from a tertiary teaching hospital in Anhui Province, China. The clinical characteristics and predictors of mortality were analyzed. Meanwhile, the bacterial isolates were characterized for drug susceptibility, multi-locus sequence typing, and drug resistance genes. Results: The multivariate analysis revealed that fiberoptic bronchoscopy (p = 0.005, OR=2.72), repeat transfusions (p = 0.008, OR= 2.23) and exposure to tigecycline (p = 0.002, OR = 6.58) were independent risk factors for CRKP and CRAB co-infection. Neutrophil ≥11.9*109 (p = 0.035, adjusted HR = 3.12) and C-reactive protein ≥ 149 mg/L (p = 0.009, adjusted HR = 4.41) were found associated with 30-day mortality. Combined neutrophil with C-reactive protein could predict 30-day mortality, of which AUC value was 0.791 (95%CI: 0.661-0.921). KPC (46/51, 90.2%) was the most common carbapenemase in CRKP. 33 isolates of CRKP belong to ST11 (33/51, 64.7%), and three new ST types ST5882, ST5883, ST5885 were detected. Conclusions: Invasive operations and antibiotics exposure can lead to CRKP and CRAB co-infection. Combined neutrophil with C-reactive protein could predict 30-day mortality.